Periodo crítico de interferencia de arvenses en el cultivo de amaranto (Amaranthus caudatus L.) en el sector la Argelia, Loja - Romero Ortega, Nancy Rocio (2021)
Amaranth (Amaranthus caudatus L.) is a traditional crop considered a superfood due to its high protein content and well-balanced amino acid profile, in addition to possessing many important agronomic characteristics such as resistance to multiple stresses, and great adaptation to different agroecological zones. One of the most important factors limiting the production of this crop is the interference of weed species, which compete for water, nutrients and solar radiation. The objective of this research was to identify the critical period of weed interference during the phenological stages in which the final grain yield of amaranth (Amaranthus caudatus L) is most affected. The trial was established at the Quinta Experimental Docente "la Argelia" located in the city of Loja, Ecuador, using a completely randomized block design with 16 treatments and three replications consisting of 8 successive periods of weed growth and 8 successive periods of growth without weeds, in which the population, cover, density and biomass of weeds were evaluated; on the other hand, the final grain yield and its components were evaluated in the amaranth crop. The dominant weeds in the crop were Galinsoga quadriradiata Ruiz y Pav, Sigesbeckia serrata DC and Brassica rapa L. Weed cover and density increased rapidly until 30 days after amaranth emergence (DDE), while weed biomass accumulated strongly until 65 DDE and continued until 105 DDE. The interference of weeds caused significant losses in yield, decreasing up to 95 %, which was explained by losses in the number of grains per plant of up to 84.32 % and losses in biomass accumulation of up to 75.16 %. The critical period of weed interference was determined between 6 and 75 DDE, located between the phenological stages of the appearance of cotyledons through the soil and the development of the inflorescence respectively, therefore, the crop must remain free of weeds during this period to avoid yield losses of more than 5 %. Key words: Weed control, weed competition, kiwicha, andean grain